22β-hydroxytingenone reduces proliferation and invasion of human melanoma cells. (August 2020) - Aranha, Elenn Suzany Pereira; da Silva, Emerson Lucena; Mesquita, Felipe Pantoja; de Sousa, Leilane Bentes; da Silva, Felipe Moura Araújo; Rocha, Waldireny C.; Lima, Emerson Silva; Koolen, Hector Henrique Ferreira; de Moraes, Maria Elisabete Amaral; Montenegro, Raquel Carvalho; de Vasconcellos, Marne Carvalho
Abstract: Melanoma is a skin cancer with high invasive potential and high lethality. Considering that quinonemethide triterpenes are described as promising anticancer agents, the aim of this study was to evaluate the effect of 22 β -hydroxytingenone (22-HTG) against human melanoma cells. Alamar blue assay was performed in order to evaluate its cytotoxic effect. Thus, subtoxic concentrations (1.0, 2.0, and 2.5 μM) were used to evaluate the effect of this compound on proliferation, migration, metabolism, and invasion. IC50 value against SK-MEL-28 cell line was 4.35, 3.72, and 3.29 μM after 24, 48, and 72 h of incubation, respectively. 22-HTG reduced proliferation, migration and invasion by melanoma cells, with decreased activity of metalloproteinases (MMP-2 and MMP-9). Futhermore, 22-HTG decreased expression of lactate dehydrogenase (LDHA), an enzyme associated with cell metabolism. Howerver, the small reduction in LDHA enzyme activity must have occurred by the cytotoxic effect of 22-HTG. According to the results, 22-HTG interferes with important characteristics of cancer, with anti-proliferative, and anti-invasive effect against melanoma cells. The data suggest that 22-HTG is an effective substance against melanoma cells and it should be considered as a potential anticancer agent. Highlights: 22-HTG has cytotoxic effect against human melanoma cells. 22-HTG reduced the proliferation of SK-MEL-28 cells at subtoxic concentrations. 22-HTG reduced migration and invasion of melanoma cells. 22-HTG decreases the activity of the MMP-2 and MMP-9 enzymes.